The Quick Guide to Wild Edible Plants : Easy to Pick, Easy to Prepare - Musselman, Lytton John, 1943- (Book collections on Project MUSE., 2013)
In this book, two botanists coach readers on how to safely identify, gather, and prepare delicious dishes from readily available plants - and indicate which ones to avoid. More than 200 color illustrations, accompanied by detailed descriptions, will help readers recognize edible plants such as nettles, daylilies, river oats, and tearthumbs.